Aportaciones de R. Sennett al desarrollo de la ética empresarial en el contexto del Nuevo Capitalismo - Muñoz Miralles, Albert (Veritas, 2017)
The objective of this article is to conduct a critical study of Richard Sennett's thinking by focusing on the contributions his work can make to develop Business Ethics. This study aims to recognise the transformations that take place in organisational terms, and are then implemented into new forms of production and work at the heart of capitalist relations, which are extremely important aspects for guiding these relations in justice, prudence and responsibility terms, as it is proposed by discourse business ethics. (English)